Encoded and Crossmodal Thermal Stimulation through a Fingertip-Sized Haptic Display - Gallo, Simon; Rognini, Giulio; Santos-Carreras, Laura; Vouga, Tristan; Blanke, Olaf; Bleuler, Hannes (Frontiers in Robotics and AI, 2015)
Haptic displays aim at artificially creating tactile sensations by applying tactile features to the user’s skin. Although thermal perception is a haptic modality it has received scant attention possibly because humans process thermal properties of objects slower than other tactile properties. Yet, thermal feedback is important for material discrimination and has been used to convey thermally-encoded information in environments in which vibrotactile feedback might be masked by noise and/or movements. Moreover, the well-reported influence of temperature over tactile processing makes thermal displays good candidates for the development of crossmodal haptic interfaces, in which temperature is used to manipulate other sensations. Here, we present a thermal display able to render four individually-controlled temperatures at the user’s fingertip along with its technical characterization and psychophysical evaluation. Device performance was assessed in terms of accuracy and repeatability. In the psychophysical evaluation, we first show that the device can render perceivable temperature gradients at the level of the fingertip, thereby extending the concept of thermally-encoded information to fingertip-sized thermal displays. Secondly, we show that increasing temperature improves stiffness precision. Results show that neglected features of thermal feedback, i.e. encoded and crossmodal thermal stimulation, can be provided by fingertip-sized thermal displays to improve haptic manipulations.